2016
DOI: 10.1590/0034-737x201663020016
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates Concentration in leaves of potato plants affected by nitrogen fertilization rates

Abstract: At poor conditions of nitrogen (N) in the soil, potato plants may accumulate starch in leaves and be indicative of N nutritional stress. The objective of this work was to determine the effects of N rates (0, 50, 100, 200 and 300 kg ha-1 of N) on the concentrations of carbohydrates (total soluble sugars-TSS, reducing sugars-RS, non-reducing sugars-NRS and starch) in the fourth leaf (FL) of two potato cultivars (Asterix and Atlantic) and their critical levels (CL) associated to the N fertilization rate necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…It has also been reported that plants increase the compounds like carbohydrates, to maintain osmotic balance and get the ability to absorb more water from the rhizosphere in order to improve osmotic adjustment (Abdalla and El-Khoshiban 2007). Soluble sugars prevent the dehydration of proteins and cell membranes due to maintaining turgidity in stressed leaves (Braun et al 2016). In this study, sugar accumulation can be considered as one of the mechanisms of drought resistance in amaranth plant because there was a significantly negative correlation (r = − 0.88**) between soluble sugars and proteins (data not shown).…”
Section: Leaf Soluble Carbohydratesmentioning
confidence: 73%
See 1 more Smart Citation
“…It has also been reported that plants increase the compounds like carbohydrates, to maintain osmotic balance and get the ability to absorb more water from the rhizosphere in order to improve osmotic adjustment (Abdalla and El-Khoshiban 2007). Soluble sugars prevent the dehydration of proteins and cell membranes due to maintaining turgidity in stressed leaves (Braun et al 2016). In this study, sugar accumulation can be considered as one of the mechanisms of drought resistance in amaranth plant because there was a significantly negative correlation (r = − 0.88**) between soluble sugars and proteins (data not shown).…”
Section: Leaf Soluble Carbohydratesmentioning
confidence: 73%
“…The reason for the reduction of soluble carbohydrates in the presence of N can be attributed to the key role of nitrogen element in the production of amino acids. The biosynthesis of amino acids requires the use of some Calvin cycle metabolites, which necessitates the consumption of the carbohydrates and their derivatives (Braun et al 2016).…”
Section: Leaf Soluble Carbohydratesmentioning
confidence: 99%
“…All three of these processes require carbohydrates because the carbohydrates that are formed will be compounded with nitrogen compounds to form protoplasm at growing points, which will affect plant height increase. The availability of carbohydrates concentration formed in plants is influenced by the nitrogen fertilization rate (Braun et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…TSS increased due to provide enough food for sprouting and respiration purposes (Kumar et al 2004). A positive correlation (r = 0.8225) was found between TSS and sucrose of potato tuber ( Figure 5) (Braun et al 2016). TSS decreased with the increasing of vermicompost levels.…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 88%